Prescription drug claims following a traumatic spinal cord injury for older adults: a retrospective population-based study in Ontario, Canada. Issue 11 (November 2018) - Guilcher, Sara; Hogan, Mary-Ellen; Calzavara, Andrew; Hitzig, Sander; Patel, Tejal; Packer, Tanya; Lofters, Aisha
Abstract Study design Retrospective cohort study. Objectives The objectives for this study were to examine the prevalence of polypharmacy for people with traumatic spinal cord injury (SCI) following injury and to determine risk factors. Setting Ontario, Canada Methods We used provincial-level administrative health services data of publicly funded healthcare encounters housed at the Institute for Clinical Evaluative Sciences, Toronto, Ontario. We examined prescription medications dispensed over a 1 year period post injury for persons 66+ years with an index traumatic SCI between 2004 and 2014. Polypharmacy was defined as being on 10 or more drug classes. Descriptive and analytical statistics were conducted. Relative risks and 95% confidence limits for factors related to polypharmacy were calculated using a robust Poisson multivariate regression model. Results We identified 418 cases of persons with traumatic SCI during the observation window. A total of 233 patients (56%) were taking at least 10 drug classes in the year following discharge from care for traumatic SCI. The mean number of drug classes taken post injury was 11 (SD = 6). Continuity of care was significantly associated with polypharmacy, with a higher continuity of care (having at least 75% of visits with the same doctor) reducing the risk of polypharmacy. The most common drugs prescribed were laxatives, opioids and cardiovascular-related drugs. Conclusion Findings suggest that polypharmacy is extensive among older adults with traumatic SCI. Persons with better continuity of care are less likely to have polypharmacy compared to those with less continuity. Sponsorship This project was funded by a Connaught New Investigator Award (University of Toronto), and the Craig H. Neilsen Foundation Psychosocial Research Pilot Grant (Grant #441259).